Analysis of Accuracy of The Use of UNI-T UTi165K Thermal Camera to Safeguard The Spread Of Covid-19 In The New Normal Era at the Polmed Telecommunication Laboratory Based on IoT (Internet of Things) - Muhammad Rusdi; Wiwinta Sutrisno (LPPM Universitas Duta Bangsa Surakarta, 2021)
One of the efforts that can be done is to detect the object of the spread of the virus, including at human body temperature. The use of a Thermal Camera in measuring human body temperature is felt to be the most effective because it can be done without touching the object being measured so that it can avoid physical contact that can actually transmit the Covid-19 virus. The development of Internet of Things (IoT) technology has recently been increasingly needed. IoT technology is generally developed as a solution to the need for improving remote monitoring via the internet. Telecommunication engineering laboratory of Medan State Polytechnic (Polmed) as a gathering place for students to carry out practicums really needs a system that can help prevent the development of the Covid-19 virus. In this study, a Covid-19 spread safety system in the new normal era at the Polmed telecommunication laboratory will be designed which uses a thermal camera to remotely measure the body temperature of students who will carry out practicum in the laboratory and the measurement results will be displayed in monitor screen. In designing this system, students will have their body temperature measured using the UNI-T UTi165K thermal camera with a measuring distance of 0.5 - 2 meters and those who can enter the laboratory room are students who have a body temperature of not more than 37.5 ° C. The system that is designed will also be equipped with an ichamber as a sterilization booth using a disinfectant that is sprayed automatically on students who are deemed fit to enter the laboratory and the automatic hand sanitizer will also be used in the laboratory room as an effort to prevent Covid-19 transmission. From the results of the discussion, it was found that the security system for the spread of Covid-19 in the new normal era at the Polmed telecommunication engineering laboratory based on IoT was successfully implemented and worked well. The UNI-T UTi165K thermal camera works well in detecting human body temperature from 0.5 to 2 meters. The average percentage of the UNI-T UTi165K thermal camera reading error for 0.5 m to 2 m is 0.352%. The UNI-T UTi165K thermal camera reading accuracy rate for 0.5 m to 2 m is 99.648%.